2013
DOI: 10.1016/j.cyto.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation associated with mechanical ventilation among extremely preterm infants

Abstract: Little evidence is available to document that mechanical ventilation is an antecedent of systemic inflammation in preterm humans. We obtained blood on postnatal day 14 from 726 infants born before the 28th week of gestation and measured the concentrations of 25 inflammation-related proteins. We created multivariable models to assess the relationship between duration of ventilation and protein concentrations in the top quartile. Compared to newborns ventilated for fewer than 7 days (N=247), those ventilated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 33 publications
1
92
0
1
Order By: Relevance
“…This finding suggests that conditions such as perinatal inflammation that result in increases in systemic pro-inflammatory cytokines could facilitate cytokines to cross the intact BBB and cause brain injury before birth even under nonischemic conditions. 6,20,22 Several aspects of our study deserve comment. We used recombinantly expressed, pure ovine IL-1β protein to study blood-to-brain transport in fetal sheep.…”
Section: Mabp (Mm Hg)mentioning
confidence: 99%
See 2 more Smart Citations
“…This finding suggests that conditions such as perinatal inflammation that result in increases in systemic pro-inflammatory cytokines could facilitate cytokines to cross the intact BBB and cause brain injury before birth even under nonischemic conditions. 6,20,22 Several aspects of our study deserve comment. We used recombinantly expressed, pure ovine IL-1β protein to study blood-to-brain transport in fetal sheep.…”
Section: Mabp (Mm Hg)mentioning
confidence: 99%
“…4,6 Conditions such as systemic inflammation in the fetus and neonate, sepsis, necrotizing enterocolitis, and mechanical ventilation in the neonate, which are associated with elevations in systemic pro-inflammatory cytokines, are also associated with later brain injury in premature infants. [20][21][22] In addition, we have recently shown that BBB dysfunction represents an important component of ischemicreperfusion related brain injury in the fetus, 12 and that the proinflammatory cytokine IL-1β contributes to this barrier dysfunction. 19 Nonetheless, although it has been suggested that systemic cytokines might gain access to the fetal brain by crossing the BBB, 4 there is a paucity of direct experimental evidence to support this concept and no quantitative data measuring BBB permeability with cytokines in the fetal or neonatal brain.…”
Section: Mabp (Mm Hg)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that even noninjurious mechanical ventilation using normal tidal volumes activates a proinflammatory transcriptional program in the uninjured lung, which can prime the lung for injury [13]. Invasive mechanical ventilation not only initiates a pulmonary inflammatory response, but also a systemic inflammatory response in preterm infants [14]. The preterm infant lung is more vulnerable during the transitional period soon after birth.…”
Section: Invasive Ventilation and Lung Injurymentioning
confidence: 99%
“…[3][4][5] Infants are particularly susceptible to mechanical ventilation-mediated tissue damage, especially in the context of systemic inflammatory responses. 6 Others have demonstrated that me-chanical ventilation can lead to changes in lung pressure and tension, resulting in inflammatory cytokine release, alveolar edema, physiologic alveolar damage, increased alveolar permeability, and alveolar collapse. 5 However, it has been demonstrated that sufficient airway humidification can reduce the incidence of ventilator-associated pneumonia, the inflammation of the nasal mucous membranes, and the incidence of postoperative pulmonary complications.…”
Section: Introductionmentioning
confidence: 99%